Challenges Identifying Domestic Violence in Chinese Judicial Practice: An Empirical Analysis of Personal Safety Protection Orders - Zheng, Rui (Violence against women, 2025)
Domestic violence is a global social issue that not only poses a significant threat to the stability of families but also has a profound impact on the physical and mental well-being of family members. In China, due to the broad criteria for defining domestic violence in the Anti-domestic Violence Law, challenges have arisen in the practical handling of domestic violence cases. The study is based on 238 civil protection order rulings available on the China Judgments Online website for the year 2021. In China, the criteria for identifying domestic violence are not only still subject to theoretical debate, but contentious viewpoints have also translated into inconsistencies in judicial practice. This study aims to further assess the underlying reasons for the difficulties in identifying domestic violence in Chinese judicial practice and to propose recommendations for improvement.